Jargon pada Turnamen Debat Daring National University Debating Championship (NUDC) 2020-2021 - Halum, Yustus Sentus; Imelda Wawuk, Imelda Wawuk (Unika Santu Paulus Ruteng, 2022)
Jargon is a collection of certain words or terms used by a group of people which meaning is only understood by the members of the community. This qualitative study aims to describe the jargons found in the National University Debating Championship (NUDC) student online debate tournament in the LLDikti XV region which involved five universities at the national level. After analyzing the findings and presenting a discussion on jargon at the 2020-2021 National University Debating Championship (NUDC) online debate tournament, it can be concluded that the jargon used is (1) words, (2) phrases, and (3) abbreviations. The total data for the forms of inner jargon is 44 (100%). The first order is word form jargon with 18 jargon items (41%), followed by abbreviations with 15 jargon items (34%), then phrase form with 11 jargon items (25%). In addition, to the need for further research on the impact of these jargons in the field of linguistics, then any future researches that involve more participants are also highly expected in order to obtain more comprehensive and deeper research results